LINGUISTIC AND CULTURAL CHARACTERISTICS OF METAPHORS IN THE LANGUAGE OF TURKISH SOURCES - Abdunazarovna , Abdujabbarova Feruza (Journal of Higher Education and Academic Advancement, 2024)
In the article, the linguistic and cultural characteristics of metaphors in the language of Turkish sources are covered based on the work "Qutadg ʼu bilig". The author states that metaphor is a means of shaping the linguistic landscape of the world, like linguistic units that bring nominative and communicative goals closer together. However, this tool, unlike others, serves to create new concepts using pre-existing meanings in the language system. Therefore, metaphor not only serves to ensure the existence of meaning, but is also a mechanism of formation of this meaning and a means of its transmission in the process of communication